Career Counselling Agoraphobic Clients - Conklin, Rod C. (Canadian Journal of Counselling and Psychotherapy, 2011)
This article describes a career counselling approach used with a sample of female clients suffering from severe phobia. Each step in the process is described and summarized as (1) exploration, (2) counselling, (3) action. Tests and procedures used are identified. The results of testing are reported as well as some implications and recommendations for practitioners.